Canadian raising: the case against reordering. (27th June 2016) - Picard, Marc
Abstract : Rule reordering as a principle of phonological change has come under heavy criticism in the recent past. A number of articles, e.g. Iverson (1973), Picard (1974), Hogg (1976), Dinnsen and Koutsoudas (1976), have been devoted to this question, endeavouring to show in one way or another that the reordering of phonological rules does not constitute a type of linguistic change. Some of the better known cases of alleged reordering have been examined, and many of these have been judged to be deficient for two main reasons: implausibility, due to the unjustified degree of abstractness involved, and inaccuracy, due to the omission or misinterpretation of crucial data. Generally, at the very least, a reasonable and plausible alternative solution has been put forth in each case.